Studi Pengaruh Variasi Fraksi Volum Filler Terhadap Sifat Mekanik Komposit Matriks Polimer (PMC) Berpenguat Cangkang Kerang Hijau (Perna Viridis L.) - Nurun Nayiroh; Kusairi Kusairi (Wahana Fisika, 2021)
A polymer matrix composite has been made to strengthen green mussel shell particles (Perna Viridis L.) as an effort to utilize the potential of green mussel waste for polymer composite filler material. The purpose of this study was to determine the effect of the volume fraction of the green mussel shell particles on the mechanical properties of polymer matrix composites. The mechanical properties tested are the tensile strength and impact strength of the Polymer Matrix Composite material. The matrix material used in this research is polyester Yucalak157 @ BQTN-EX with Methyl Ethyl Keton Peroxide as catalyst and filler material in the form of 100 mesh green mussel shell particles with a variation of the filler volume fraction of 10%, 20%, 30% and 40%. This composite manufacturing method is to use the hand lay up method. The results of this study, obtained tensile strength values between 32.81-39.77 MPa where the highest tensile strength was found in specimens with a filler volume fraction of 40% and the lowest in specimens with a filler volume fraction of 10%; and impact strength (ductility) between 0.190-0.317 J / mm2 where the highest impact value was found in the test sample with a filler volume fraction of 10% and the lowest was in the specimen with a filler volume fraction of 40%. The increase in tensile strength value is influenced by the addition of a larger filler composition. On the other hand, the durability / impact price decreases with the increase in filler given. Based on microstructural observations, the greater the filler composition added to the matrix can reduce the size of the voids formed in the composites that have been made, it can be interpreted that the distribution of fillers is more evenly distributed.